The potential of silver nanoparticles to control Rhizoctonia solani (AG3-PT) growth in vitro - HARTATI OKTARINA; JAMES WOODHALL; IAN SINGLETON (Jurnal Natural, 2021)
Silver nanoparticles (AgNPs) have known anti-microbial properties and therefore have the potential to be used to control fungal plant pathogens. In this study we investigated the growth of a plant pathogenic fungus, Rhizoctonia solani (AG3-PT) in the presence of AgNPs. The effect of AgNPs at two different levels (20 and 50 mg L-1) on hyphal growth and sclerotium production and viability in R. solani was investigated. The results showed that at 20 mg AgNPs L-1 R. solani hyphal growth was reduced along with the production of sclerotia. The results indicate that AgNPs have the potential to control R. solani growth and subsequent development of plant disease symptoms.